Evaluation of the Neuroprotective Effect of Lawsonia inermis Flower Extract in Alzheimer’s Disease-induced Zebrafish Model - Kavitha Ramasamy; K. Priya Gayathri; Binoy Varghese Cheriyan; I. Glory Josephine; V. D. Deepti (World Journal of Traditional Chinese Medicine)
Objective: The study aimed to evaluate the effect of Lawsonia inermis flower extract in an Alzheimer’s disease (AD)-induced zebrafish model. Materials and Methods: A total of 60 adult fishes were segregated into five groups (n = 12) and treated with various dilutions of L. inermis extract, respectively. The study was conducted in two phases. The effective dilution range was identified in Phase I (7 days), and the respective dilution was used in Phase II (14 days) for sodium valproate-induced AD. The treatment groups were screened for anxiety, motor coordination, and memory using a novel tank diving test, swim velocity, and maze test, respectively. Treated fishes from each group were investigated for histopathology examination. The results were analyzed with a one-way analysis of variance followed by a post hoc Tukey multiple comparison test using GraphPad Prism. Results: In Phase I, a dose-dependent reduction of degeneration was observed in the pathology of the brain with no significant changes in cognition. In Phase II, the effective dose (8 μg/day/0.5 mg fish) of L. inermis flower extract has shown a significant reduction in anxiety, degeneration, and motor dysfunction with a significant increase in memory and learning. Conclusions: The current investigation has shown that the L. inermis flower extract has a neuroprotective impact on AD zebrafish.